2023
DOI: 10.1038/s41419-023-05733-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of N-glycosylation modification in the pathogenesis of liver cancer

Abstract: N-glycosylation is one of the most common types of protein modifications and it plays a vital role in normal physiological processes. However, aberrant N-glycan modifications are closely associated with the pathogenesis of diverse diseases, including processes such as malignant transformation and tumor progression. It is known that the N-glycan conformation of the associated glycoproteins is altered during different stages of hepatocarcinogenesis. Characterizing the heterogeneity and biological functions of gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 146 publications
(149 reference statements)
0
15
0
Order By: Relevance
“…CD44 was identified with five phosphosites and two N -glycosites. N -glycosylation of CD44 has reported to affect its interaction with hyaluronic acid [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…CD44 was identified with five phosphosites and two N -glycosites. N -glycosylation of CD44 has reported to affect its interaction with hyaluronic acid [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…The field of proteoglycomics has shown that changes in proteoglycan are closely linked to liver diseases, although most research focuses on hepatocellular carcinoma and viral liver diseases. 33,34 There is a lack of studies on NAFLD and serum glycopatterns, making systematic research on serum glycopatterns of NAFLD patients and the development of diagnostic models combined with machine algorithms highly significant for early screening of NAFLD. This study collected 170 serum samples to analyze changes in NAFLD serum glycopatterns and develop diagnostic models using different algorithms.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Glycosylation is one of the most prevalent post-translational modifications and involves in many fundamental molecular and cell biology processes occurring in cancer, including tumor cell dissociation and invasion, tumor cell–matrix interactions, cell signaling transduction pathways, inflammation and immune response. 14 , 15 It was reported that protein glycosylation was associated with the pathogenesis of many cancers, such as gastric cancer, colorectal cancer, and hepatocellular carcinoma. 14 , 16 , 17 , 18 , 19 , 20 Particularly, glycans play important role in immunosurveillance, with most of the key factors involved in immune response are glycosylated.…”
Section: Introductionmentioning
confidence: 99%
“… 14 , 15 It was reported that protein glycosylation was associated with the pathogenesis of many cancers, such as gastric cancer, colorectal cancer, and hepatocellular carcinoma. 14 , 16 , 17 , 18 , 19 , 20 Particularly, glycans play important role in immunosurveillance, with most of the key factors involved in immune response are glycosylated. 15 , 21 , 22 , 23 Previous studies demonstrated that antitumor immunity was an important barrier to tumor formation and progression, while evading immune destruction have been listed as an emerging hallmark of cancer.…”
Section: Introductionmentioning
confidence: 99%